Pathways to Integration: The Dialogical Approach - Julia Underwood; Rebecca Havens (Christian Business Academy Review, 1970)
This paper introduces the distinctive and value of a “Dialogical Approach” to faculty development methods in Christian faith integration from the authors’ experiences in developing, planning, and executing a successful one-day dialogical conference series over three consecutive years. Critical elements, lessons learned, and evidence of various outcomes are discussed in an effort to support leaders and faculty in Christian business education settings to better assist their faculty in Christian faith integration efforts in the classroom and scholarship in business disciplines. The Dialogical Approach has proven to be an effective and synergistic paradigmatic shift in faculty development methods of faith integration.